CircPAPPA2 plays a role in preeclampsia pathogenesis via regulation of the miR-942/miR-5006-3p - Wenyan Liao; Huan Zeng; Xinmiao Jiang; Xin Deng; Shun Tu; Hui Lan; Lingling Tang; Weilei Dong; Chengming Ding (BMC, 2024)
Abstract CircRNAs are a class of endogenous non-coding RNAs implicated in the pathogenesis of many pregnancy related diseases, one of which is pre-eclampsia (PE). This study aims to investigate the role of CircPAPPA2 (circbase ID: hsa_circ_0015382) in regulating the migration and invasion of trophoblast cells. RNA sequencing was used to identify the differentially expressed circRNAs in placenta of PE and normal pregnant women. Quantitative polymerase chain reaction (qRT-PCR) was used to verify the expression of circPAPPA2 and two miRNAs (miR-942-5p, 5006-3p) in placenta of PE and normal pregnant women. CCK8 and transwell experiments were performed to assess the function of circPAPPA2 in PE development.The interaction between circPAPPA2 and miR-942-5p/miR-5006-3p was verified by dual-luciferase reporter assay. Finally, bioinformatics analyzed with gene ontology, Kyoto Encyclopedia of the target genes. The results showed that the expression of circPAPPA2 was increased in placenta of PE pregnant women. Also, circPAPPA2 impedes trophoblasts cell proliferation and invasion. Moreover, the expression of circPAPPA2 was positively correlated with systolic blood pressure and urine protein. In addition, circPAPPA2 serves as a sponge of miR-942-5p and miR-5006-3p. In conclusion, CircPAPPA2 regulates trophoblasts cell proliferation and invasion by mediating the miR-942/miR-5006-3p.